Effect on Fatigue Performance of Residual Stress induced via Laser Shock Peening in Mechanically Damaged 2024‐T351 Aluminium Sheet - Smyth, Niall (Cranfield University, 2014)
During manufacture and maintenance the fuselage skin of aircraft are susceptible to damage in the form of scratches. Normally not considered to be of major concern to aircraft structural integrity some airlines discovered fatigue cracks had initiated at the root of scratches. Crack propagation was in the through thickness direction and if left untreated could cause rapid decompression of the passenger cabin. Standard repair methodology requires patches be riveted around scratch damage and in extreme cases could require entire replacement of affected skin panels. Laser shock peening (LSP) is an emerging surface treatment that has been shown to improve fatigue performance of safety critical components by inducing a surface layer of compressive residual stress. In this work LSP was applied along the scratch damage in an effort to restore pristine fatigue performance. The aim of the project was to model the effect on fatigue crack growth rate of residual stress fields induced via LSP and to validate predictions by comparison to experimental test results. The scratches were recreated under controlled laboratory conditions using a diamond tipped tool. This process allowed creation of reproducible V shaped scribes to controlled depth, wall angle and root radius. Scribes of depth 50 and 150 μm with root radius 5 μm were created in dogbone shaped samples of 2 mm thick 2024‐T351 clad aluminium. Samples were tested in fatigue at an R = 0.1 and maximum stress of 200 MPa. The scribe damage reduced fatigue life compared to the pristine material by a factor of 22. Scribed samples were processed using LSP treatment from different providers that created known residual stress fields in the material. The fatigue life of scribed samples after peening varied from a further decrease to a 13 times increase dependent on the residual stress field induced. An elastic‐plastic crack closure based finite element model was created to determine the effect on stress intensity factor and stress ratio of residual stress. Fatigue lives calculated were within a factor of 2 of experimental lives. It was predicted that crack closure was present during up to 80% of the applied load cycle due to the compressive residual stress field. However plasticity induced crack closure actually reduced after peening because the compressive residual stress field induced a smaller plastic zone at the crack tip and hence reduced the plastic wake. A residual stress based fatigue life sensitivity study was performed to optimise the profile of the residual stress field for improved fatigue performance. The required profile was created in test samples using LSP. The fatigue life of peened samples increased by a factor of up to 15 however pristine life was not fully recovered. A restriction imposed by the industrial application was peening applied to one face only. This created an unbalanced stress field that resulted in sample distortion to maintain equilibrium. The distortion induced out of plane bending stresses during testing and caused premature crack initiation on the unpeened face. However using interrupted fatigue tests it was found that although crack initiation also occurred at the root of the scribes the cracks were arrested after 24 μm of propagation. This was consistent with the findings of the crack growth prediction model.